Prevalence of PTSD and depression, and associated sexual risk factors, among male Rwanda Defense Forces military personnel. Issue 8 (22nd May 2013) - Harbertson, Judith; Grillo, Michael; Zimulinda, Eugene; Murego, Charles; Cronan, Terry; May, Susanne; Brodine, Stephanie; Sebagabo, Marcellin; Araneta, Maria Rosario G.; Shaffer, Richard
Abstract Objectives To assess depression and PTSD prevalence among the Rwanda Defense Forces (RDF) and evaluate whether sexual risk behaviour, STIs, HIV and alcohol use were significantly higher among those who screened positive. Methods Consenting active‐duty male RDF personnel, aged ≥21 years, completed an anonymous sexual risk survey linked to HIV rapid testing that included standardised assessments for PTSD (PCL‐M), depression (CES‐D) and alcohol use (AUDIT). PTSD and depression prevalence were calculated (data available for 1238 and 1120 participants, respectively), and multivariable regression analyses were conducted. Results 22.5% screened positive for depression, 4.2% for PTSD and 3.4% for both. In adjusted analyses, odds of either depression or PTSD were significantly higher in participants reporting STI symptoms (OR = 2.27, 2.78, respectively) and harmful alcohol use (OR = 3.13, 3.21, respectively). Sex with a high‐risk sex partner, lower rank and never deploying were also significantly associated with depression in adjusted analyses. Conclusions Nearly one‐fourth of RDF participants screened positive for PTSD or depression, which impacts sexual risk behaviour, HIV acquisition risk and military readiness. Findings may extend to other deploying militaries and provide additional evidence of an association between mental health status and sexual risk behaviour. Effective mental health treatment interventions that also include alcohol use assessments, STI identification/treatment and sexual risk behaviour reduction are needed.